Improving The Professionalism Of Teachers By Understanding The Philosophy Of Education And Implementing The Professional Code Of Ethics - Maharani, Intan (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
Education is a means of acquiring knowledge. In this context, a teacher or educator serves as a guide. Not a few teachers violate and ignore the Teachers' Code of Ethics, even though the Teachers' Code of Ethics is very important for the world of education. Whatever the profession, there must be binding standards to ensure that the profession and the teaching profession are well run. Professional teachers are certainly bound by the existing code of ethics, but unfortunately there are still many teachers with professional teacher certification who do not reflect professionalism and violate the teacher code of ethics. This paper aims to respond to the concerns of educational practitioners who feel that there are still many people who do not act and behave in accordance with the rules. Therefore, it is very important to understand and respect the professional code of ethics, especially in the teaching profession, because by understanding and respecting the professional code of ethics that has been established, doing work and service will feel very happy. The enforcement of this code of ethics must also be based on constructive principles, among others: Tut Wuri Handayani Principle, Justice Principle, Family Principle, Communication Principle and Teacher Principle. These principles are in line with the philosophy of education initiated by philosophers of education.